The role of mir-511-3p in modulating human dendritic cell function - Awuah, Dennis Kwadwo Kyeremeh (2019)
MicroRNAs (miRNA) are functional, non-coding RNA molecules that negatively regulate gene expression by repressing target mRNAs. Recently, microRNA-511-3p (miR-511-3p) has emerged as a key player in regulating the function of human DCs and in controlling TLR4-mediated signalling. Previously, our group showed that c-type lectin receptors on DCs such as the mannose receptor (MR) is involved in uptake of allergens and downstream events leading to Th2 allergic responses. Interestingly, miR-511-3p is embedded within the MRC1 gene that encodes MR. Therefore, in this study, it was hypothesised that miR-511-3p maybe a key player in regulating MR expression on DCs and downstream events affecting Th polarisation. Additionally, miR-511-3p is highlighted to putatively target PPARγ, a potent suppressor of immune responses; however the link between miR-511-3p and PPARγ and its influence on DC function within the context of LPS-induced inflammatory responses is unknown.